2011
DOI: 10.1098/rspb.2011.2268
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relatedness as a tool in restoration ecology: a meta-analysis

Abstract: Biotic interactions assembling plant communities can be positive (facilitation) or negative (competition) and operate simultaneously. Facilitative interactions and posterior competition are among the mechanisms triggering succession, thus representing a good scenario for ecological restoration. As distantly related species tend to have different phenotypes, and therefore different ecological requirements, they can coexist, maximizing facilitation and minimizing competition. We suggest including phylogenetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 53 publications
6
126
1
2
Order By: Relevance
“…On the other hand, another metaanalysis that related interspecific competition to phylogenetic and phenotypic characteristics found that increasing phylogenetic distance and life form disparity between nurse (i.e., neighbor) and target plants could promote successful nursebased restoration (Verdu et al 2012). Furthermore, Violle et al (2011) provided strong empirical evidence supporting the PLSH, by showing that interspecific interactions are more confidently predicted through phylogenetic relatedness than functional traits.…”
Section: Communicated By Iris C Andersonmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, another metaanalysis that related interspecific competition to phylogenetic and phenotypic characteristics found that increasing phylogenetic distance and life form disparity between nurse (i.e., neighbor) and target plants could promote successful nursebased restoration (Verdu et al 2012). Furthermore, Violle et al (2011) provided strong empirical evidence supporting the PLSH, by showing that interspecific interactions are more confidently predicted through phylogenetic relatedness than functional traits.…”
Section: Communicated By Iris C Andersonmentioning
confidence: 99%
“…The bladj algorithm was used to date the nodes of the phylogenetic tree based on the ages from the Wikstrom et al database (Wikstrom et al 2001) using the Phylocom software (Webb et al 2008) (Supplementary material S1). For non-vascular plants, we estimated phylogenetic distance between target and neighbor species using the online TimeTree application (Hedges et al 2006;Verdu et al 2012). We also calculated the delta stress effect score, which is the difference between the effect size of low and high stress levels on growth or survival (i.e., the effect size under high stress − the effect size under low stress), and the stress variance score, which was the sum of the variances of growth or survival measurements at high and low stress (Borenstein et al 2009;He et al 2013).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on several assumptions, the phylodiversity of species assemblages also provides insights into processes of community assembly (Graham et al, 2009;Verdú et al, 2012;Meiners et al, 2015). Assuming that phylogenetic relatedness is a proxy for ecological relatedness (but see Gerhold et al, 2015;Lososová et al, 2016), the comparison of the phylodiversity of real assemblages with randomly constructed assemblages allows the relative importance of ecological processes to be inferred.…”
Section: Introductionmentioning
confidence: 99%